Admission biomarkers among patients with acute myocardial-infarction related cardiogenic shock with or without out-of-hospital cardiac arrest. (26th April 2021) - Thoegersen, M; Frydland, M; Helgestad, O; Jensen, LO; Josiassen, J; Goetze, JP; Moeller, JE; Hassager, C
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Lundbeck Foundation OnBehalf: Critical Cardiac Care Research Group Background: Approximately half of all patients with acute myocardial infarction complicated by cardiogenic shock (AMICS) present with out-of-hospital cardiac arrest (OHCA). Cardiogenic shock due to OHCA is caused by abrupt cessation of circulation, whereas AMICS without OHCA is due to cardiac failure with low cardiac output. Thus, there may also be differences between the two conditions in terms of blood borne biomarkers. Purpose: To explore the potential differences in the admission plasma concentrations of biomarkers reflecting tissue perfusion (lactate), neuroendocrine response (mid-regional proadrenomedullin [MRproADM], Copeptin, pro-atrial natriuretic peptide [proANP]), endothelial damage (Syndecan-1, soluble thrombomodulin [sTM]), inflammation (soluble suppression of tumorigenicity 2 [sST2]) and kidney injury (neutrophil gelatinase-associated lipocalin [NGAL]), in patients with AMICS presenting with or without OHCA. Method: Consecutive patients admitted for acute coronary angiography due to suspected ST-elevation myocardial infarction (STEMI) were enrolled during a 1-year period. A total of 2, 713 patients were screened. In the present study 86 patients with confirmed STEMI and CS at admission were included. Results: Patients with OHCA (had significantly higher median admission concentrations of Lactate (6, 9 mmol/L vs. 3.4 mmol/L p <0.001), NGAL (220 ng/ml  vs 150 ng/ml p = 0.046), sTM (10 ng/ml vs. 8.0  ng/ml p = 0.026) and Syndecan-1 (160 ng/ml vs. 120 ng/ml p= 0.015) and significantly lower concentrations of MR-proADM (0.85 nmol/L  vs. 1.6 nmol/L p <0.001) and sST2 (39 ng/ml vs. 62 ng/ml p < 0.001).  After adjusting for age, sex, and time from symptom onset to coronary angiography, lactate (p = 0.008), NGAL (p = 0.03) and sTM (p = 0.011) were still significantly higher in patients presenting with OHCA while sST2 was still significantly lower (p = 0.029). There was very little difference in 30-day mortality between the OHCA and non-OHCA groups (OHCA 37% vs. non-OHCA 38%). Conclusion: Patients with STEMI and CS at admission with or without concomitant OHCA had similar 30-day mortality but differed in terms of Lactate, NGAL, sTM and sST2 levels at the time of admission to catheterization laboratory. These findings propose that non-OHCA and OHCA patients with CS could be considered as two individual clinical entities.